Development of Discovery Learning Tools to Facilitate Junior High School Students’ Mathematical Understanding Ability - Achid Albintani; Atma Murni; Syarifah Nur Siregar (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2023)
This research and development (R&D) aim to produce learning tools in the form of syllabus, lesson plans (RPP), and student worksheets (LKPD) based on discovery learning models on geometry flat-side materials to facilitate the mathematical understanding ability of 8th-grade students of junior high school that has met the valid and practical requirements. The development model used is 4-D, consisting of four stages: Define, Design, Development, and Disseminate. The research instruments used in this research are validity instruments in the form of validation sheets and practicality instruments in the form of student response questionnaires. The syllabus, RPP, and LKPD that has been developed are validated by three validators and then tested out. According to data analysis of validation results, learning tools have met the valid requirements with an average score syllabus of 3.93, RPP of 3.86, and LKPD of 3.80. The student response questionnaire showed that the practicality of LKPD has met the practical requirements with an average score of in small group trials 3.61 and large group trials 3.53. Thus, the learning tools developed have met the valid and practical requirements to be used by 8th-grade students of junior high school.